Novel hole-pillar spacer design for improved hydrodynamics and biofouling mitigation in membrane filtration - Adnan Qamar (Nature Portfolio, 2021)
Abstract Feed spacers are the critical components of any spiral-wound filtration module, dictating the filtration performance. Three spacer designs, namely a non-woven commercial spacer (varying filament cross-section), a symmetric pillar spacer, and a novel hole-pillar spacer (constant filament diameter) were studied using Direct Numerical Simulations (DNS), 3-D printed and subsequently experimentally tested in a lab-scale ultrafiltration set-up with high biofouling potential feed water at various feed pressures. Independent of the applied pressure, the novel hole-pillar spacer showed initially the lowest feed channel pressure drop, the lowest shear stress, and the highest permeate flux compared to the commercial and pillar spacers. Furthermore, less biofilm thickness development on membrane surface was visualized by Optical Coherent Tomography (OCT) imaging for the proposed hole-pillar spacer. At higher feed pressure, a thicker biofilm developed on membrane surface for all spacer designs explaining the stronger decrease in permeate flux at high pressure. The findings systematically demonstrated the role of various spacer designs and applied pressure on the performance of pre-treatment process, while identifying specific shear stress distribution guidelines for engineering a new spacer design in different filtration techniques.